2023
DOI: 10.3390/jfb14020072
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin/Honey-Incorporated Alginate Hydrogel as a Bio-Based pH-Responsive/Antibacterial/Antioxidant Wound Dressing

Abstract: Infection is a major problem that increases the normal pH of the wound bed and interferes with wound healing. Natural biomaterials can serve as a suitable environment to acquire a great practical effect on the healing process. In this context, anthocyanin-rich red cabbage (Brassica oleracea var. capitata F. rubra) extract and honey-loaded alginate hydrogel was fabricated using calcium chloride as a crosslinking agent. The pH sensitivity of anthocyanins can be used as an indicator to monitor possible infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A dropwise addition of a 0.1 M CaCl 2 solution was then incorporated into the ALG solution with continuous stirring to achieve a final concentration of 36 mM. The resulting solution was then poured into a Petri dish and put at room temperature for 24 h to form hydrogel films …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dropwise addition of a 0.1 M CaCl 2 solution was then incorporated into the ALG solution with continuous stirring to achieve a final concentration of 36 mM. The resulting solution was then poured into a Petri dish and put at room temperature for 24 h to form hydrogel films …”
Section: Methodsmentioning
confidence: 99%
“…The resulting solution was then poured into a Petri dish and put at room temperature for 24 h to form hydrogel films. 37 2.4. Electrospinning.…”
Section: Emulsion Preparationmentioning
confidence: 99%
“…Recent research has demonstrated the versatility of these materials that allow the easy incorporation of multiple active agents. For instance, Lotfinia et al [ 42 ] combined alginate in the form of a hydrogel with honey and red cabbage extract, and could observe improved mechanical properties, the antibacterial activity attributed to the honey, as well as the antioxidant properties and good activity against pH changes from the red cabbage.…”
Section: Anthocyanin-loaded Polymers: Preparation and Characterizatio...mentioning
confidence: 99%
“…Moreover, they are preferable for pH‐sensing applications due to their easy integration into the nanofibre structure. Up to now, numerous studies have been performed on their usage as wound healing monitoring 14–18 . The studies showed that the anthocyanin‐loaded nanofibre mats could sense pH changes and be successfully used as a wound dressing material.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, numerous studies have been performed on their usage as wound healing monitoring. [14][15][16][17][18] The studies showed that the anthocyanin-loaded nanofibre mats could sense pH changes and be successfully used as a wound dressing material.…”
mentioning
confidence: 99%